Understanding recruitment choices : the role of applicant and recruiter characteristics - Minßen, Luisa [Verfasser] (ROA, 2025)
"This dissertation explores the mismatch between the supply of apprenticeship applicants and mid-qualified workers and the demand from firms. It investigates how socio-economic and institutional factors contribute to unequal access to employment opportunities and examining the issue at three levels: institutional, firm, and individual. This research focuses on the demand side of the labour market, examining the role of recruiters and firms in shaping recruitment decisions. At the institutional level, the study assesses the effectiveness of active labour market policies (ALMPs) in supporting low-skilled applicants. At the firm level, it explores how product-innovating firms prioritise personality traits in recruiting mid-qualified workers. At the individual level, the dissertation examines how recruiter characteristics influence gender discrimination in apprenticeship recruitment for gender-segregated occupations. Findings suggest that financial support increases the recruitment of low-skilled applicants, certain personality traits are important for product-innovating firms, and recruiter preferences impact gender biases in recruitment. The study highlights the need for targeted interventions to improve access to high-quality employment opportunities." (Authors' abstract, BIBB-Doku)
Keywords: S 5.3 Personalentwicklung; 370; Bewerberauswahl; Personalpolitik; Ausbildungsstellenbewerber; Geringqualifizierter; Produktinnovation; Persönlichkeitsmerkmal; Geschlechtersegregation